2005
DOI: 10.1063/1.1880972
|View full text |Cite
|
Sign up to set email alerts
|

Hole localization in [AlO4] defects in silica materials

Abstract: First-principles calculations based on cluster models have been performed to investigate the ground state and the optically excited states of the [AlO(4)](0) hole in alpha-quartz and in the siliceous zeolite ZSM-5. The structure and spectroscopic properties of this defect have been studied using the recently developed Becke88-Becke95 one-parameter model for kinetics (BB1K) functional of Zhao et al., [J. Phys. Chem. A 108, 2715 (2004)]. Our results show that the BB1K method is significantly more reliable and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
65
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 54 publications
10
65
0
Order By: Relevance
“…This defect is believed to cause the smoky coloration of quartz crystals 2,7 . On theoretical level, this 'classical' model has been confirmed by cluster calculations on unrestricted Hartree-Fock or hybrid functional level [8][9][10][11] , yielding a polaronic hole localization and hyperfine coupling constants with 27 Al, 17 O and 29 Si in good agreement with experiments. It was shown that the defect undergoes local symmetry breaking and Jahn-Teller reconstruction with one oxygen atom relaxing away from the Al ion.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…This defect is believed to cause the smoky coloration of quartz crystals 2,7 . On theoretical level, this 'classical' model has been confirmed by cluster calculations on unrestricted Hartree-Fock or hybrid functional level [8][9][10][11] , yielding a polaronic hole localization and hyperfine coupling constants with 27 Al, 17 O and 29 Si in good agreement with experiments. It was shown that the defect undergoes local symmetry breaking and Jahn-Teller reconstruction with one oxygen atom relaxing away from the Al ion.…”
Section: Introductionsupporting
confidence: 62%
“…Correspondingly, the Al-O bond lengths in this case are very similar. On the other hand, To et al 11 found a bond elongation of 12% using the BB1K functional (42% HF exchange), whereas Pacchioni et al 10 reported a 14% elongation from their 100% Hartree-Fock calculations. Our cluster calculations using the BHandHLYP hybrid functional (50% exact exchange) yield spin localization and defect geometry very similar to our sX-LDA results.…”
Section: Resultsmentioning
confidence: 99%
“…21 For instance, To et al found that a semi-empirical hybrid functional including 42% of EXX (called BB1K functional) yields the correct picture. 22 In view of the preceding work, it may be concluded that some amount of empiricism is required to tackle the Alimpurity problem within DFT, casting doubts on its actual predictive power. Recently, a rationale for the value that the EXX fraction takes in extended systems has been put forward.…”
Section: Introductionmentioning
confidence: 99%
“…A number of electronic structure methods are able to restore the qualitative picture of single-site localization, e.g., self-interaction correction (SIC) [4,5], DFT+U [6,9], and hybrid-DFT [10,11].…”
mentioning
confidence: 99%